A note on \(δ\)-Jordan homomorphism on Banach algebras - Zivari-Kazempour, Abbas (Global Journal of Mathematical Analysis, 2014)
In this paper we show that, under special hypotheses, each \(δ\)-Jordan homomorphism \(φ\)Â between Banach algebras A and B is continuous and almost multiplicative.Keywords:Â \(δ\)-Jordan homomorphism, almost multiplicative, Semisimple.